Protectionism in international insurance transactions - Richard Senti (Intereconomics, 1986)
Efforts have been in progress for a number of years now to conclude an agreement on the regulation of international trade in services, including international insurance activities. The proposals put forward by the OECD, UNCTAD and GATT differ considerably from one another, as do those put forward by individual countries. How important is international insurance? What trade barriers exist today? What reforms have been proposed and what is the likelihood of their being realized?
Keywords: 330; Service Transactions